Specific features of dielcometric water determination in alcohols used in synthesis and analysis of functional materials - Blank, T.A.; Eksperiandova, L.P.; Sidletsky, O.Ts.; Kasyan, N.A.; Lisetsky, L.N. (Functional Materials, 2008)
Water determination procedures have been developed for ethanol, methanol, and isopropanol using a special dielcometric cell. Metrological characteristics of titrimetric (under visual detection of end point) and dielcometric methods of water determination in those alcohols have been compared. The combination of both methods has been shown to provide a highly reliable analysis of alcohols at both very low and very high water content. The procedures can be used in extraction/dielcometric and extraction/titrimetric water determination in functional materials.